2005
DOI: 10.1111/j.1469-7610.2005.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of temporal synchrony in intermodal events by children with autism and children with developmental disabilities without autism

Abstract: Several explanations are offered for this apparently autism-specific, language-specific pattern of responding to temporal synchrony, and potential developmental sequelae are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
146
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(171 citation statements)
references
References 34 publications
24
146
1
Order By: Relevance
“…These results indicate that the subjects with ASD did integrate the auditory and visual information, probably at an early (sensory) level of processing. Our findings are in accordance with the results from a recent study, indicating normal discrimination of temporal synchrony in non-linguistic intermodal stimuli in mentally retarded young children with ASD (Bebko, Weiss, Demark, & Gomez, 2006) and studies indicating that patients with ASD show normal integration of visual and auditory speech stimuli (e.g. Williams, Massaro, Peel, Bosseler, & Suddendorf, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that the subjects with ASD did integrate the auditory and visual information, probably at an early (sensory) level of processing. Our findings are in accordance with the results from a recent study, indicating normal discrimination of temporal synchrony in non-linguistic intermodal stimuli in mentally retarded young children with ASD (Bebko, Weiss, Demark, & Gomez, 2006) and studies indicating that patients with ASD show normal integration of visual and auditory speech stimuli (e.g. Williams, Massaro, Peel, Bosseler, & Suddendorf, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…135 Mother-infant synchrony itself predicts wide-ranging later developments. [135][136][137] Temporal synchrony/reciprocity difficulties of autism [49][50][51] have also been recorded in autistic infancy, 52,138,139 where they may serve as a functional deficit contributing to the developmental cascade of autistic disorder. 21,22,44,140,141 Problems in timing, memory and sleep are all characteristics of autistic disorder and aspects of timing, memory and sleep are each clock-generegulated in other species.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] They also extend to the reciprocity/temporal synchrony skills required for conversation. [49][50][51][52] Objectively recorded atypical sleep architecture in young adults with high-functioning autism and Asperger syndrome 53 and in children with autistic disorder 54 shows association between sleep profiles and autistic symptomatology. 53,54 Circadian hormone (melatonin) anomalies are found in autistic disorder [55][56][57] as well as altered serotonin levels in autism.…”
Section: Timing Difficulties and Autismmentioning
confidence: 99%
“…For example, some evidence suggests that individuals with autism differ from neurotypical peers in the way they process, integrate, and attend to multisensory information (see Bahrick, 2010;Iarocci & McDonald, 2006;Leekam et al, 2007 for reviews). More specifically, individuals with autism have been shown to be less sensitive to amodal properties in contexts of intersensory redundancy compared to typically developing peers, including in the integration of audio-visual speech (e.g., Smith & Bennetto, 2007;Magnee, de Gelder, van Engeland, Kemner, 2008), susceptibility to the McGurk effect (de Gelder, Vroomen, & van der Heide, 1991;Mongillo et al, 2008;Williams, Massaro, Peel, Bosseler, & Suddendorf, 2004), and processing of audio-visual temporal synchrony in some contexts (e.g., Bebko Weiss, Denmark, Gomez, 2006;Mundy & Burnette, 2005). Bahrick (2010) has suggested that autism itself may fundamentally be an impairment in early Intersensory Perception 30 intersensory processing, ultimately giving rise to later higher-level social and linguistic impairments, due, in part, to the early different or disrupted attentional biases that reduce attention towards important amodal properties of human social and communicative situations.…”
Section: Translational Relevance To Studying Multisensory Processingmentioning
confidence: 99%